A New Model for Enhancing Student Portal Usage in Saudi Arabia Universities - Alatawi, S. S. T.; Miskon, S.; Abdullah, N. S.; Ghabban, F.; Saeed, F.; Alfadli, I.; Ameerbakhsh, O. (Engineering, Technology & Applied Science Research, 2021)
Portals are gateways that provide users with the information they need from different sources and display it on a single page. It is important to see that universities utilize the resources and services provided by their student portals. With the rapid development of Information and Communication Technology (ICT), the Ministry of Education in Saudi Arabia aims to develop and improve student portals by providing high-quality teaching services through the university portal systems. This paper discusses the importance of student portal usage in Saudi Arabian universities and investigates the factors that influence the utilization of student portals as perceived by the students of the Saudi universities. Based on these factors, a model is proposed which identifies students’ expectations about the Saudi university portals. A quantitative methodology was employed to develop the model. The results revealed that 8 out of 10 factors of the model are significant and positively affect student portal usage. The enhancement of student portals based on the identified significant factors will assist the universities to increase their utilization and their provided services.